PENERAPAN ASAS KESEIMBANGAN DALAM PERJANJIAN KREDIT RUMAH - Windi Arista (Fakultas Hukum Universitas IBA Palembang, 2022)
Home is a basic need of every human being. The house has a very important function for humans, namely as a shelter from all weather and as a place to build a family and as a place to carry out various business activities. In order to accommodate the community's need to own a house, the banking sector offers a Home Ownership Credit facility, which in this discussion will be abbreviated as KPR. KPR is a credit facility provided by banks to individual customers who will buy or repair a house. At the implementation stage of the implementation of the KPR Agreement, there may be